(untitled) (Revista Apotheke, 2021)
The precarious and, at the same time, privileged situation of art creation and the education of the arts has offered multiple possibilities for a long time, as it is precisely under continuous review. For this reason, we could find contributions about what the arts can teach to education, and also about how contemporary arts are developing themselves in the education territories. In such a particular situation, gender and sexuality issues are building bridges as common interests, particularly in the teacher-training field. This article is framed in this context and offers a review of the author’s own trajectory to reflect, together with a group of former students, on a specific teaching/learning experience that took place during the creation of an installation that aimed to break the normative gender roles.